Examining factors influencing students digital citizenship level and realationship of online mediation and digital citizenship - Noor Saidatul Akmal Sukarno (2021)
Present lower secondary students are the digital citizens known as Generation Z. Theincreasing rate of digital device ownership among students has led to an increase inunethical use of technology. As students are active Internet users, digital citizenshipand online mediation are vital in developing healthy digital practices. Hence, this studywas conducted to examine lower secondary students' digital citizenship levels usingthe REP (Respect, Educate and Protect) framework as well as identify the effects ofdigital device usage experience, which refers to years of digital device usage and theaverage of daily Internet usage on the students' digital citizenship levels in terms ofREP. In addition, the relationship between online mediation and digital citizenship levelwas determined in this study. A survey was conducted using a quantitative approach.An adapted questionnaire was distributed to 374 students of Form 1 and 2 studentswho were selected from the Sepang district using the stratified random samplingmethod. The data were analysed using SPSS software by conducting descriptivestatistics, MANOVA and Pearson's correlation. Findings revealed a high average level(mean = 3.79) of digital citizenship among the students. However, the students scoredthe lowest mean in digital access (mean = 3.40, SD = .59) and digital communication(mean = 3.44, SD = .52). Meanwhile, the students' years of digital device usage (p =.137) and the average of daily Internet usage (p = .327) were found to have nosignificant effect on the digital citizenship level. The correlation analysis found amoderate positive relationship (r = .476) between online mediation and the students'digital citizenship level. Conclusively, digital citizenship and online mediation couldhelp students to be responsible digital citizens. The implication of this study indicatesthe need to disseminate digital citizenship through education to nurture students' goodonline behaviour.